Pengaruh Profitabilitas, Likuiditas, dan Leverage terhadap Pengungkapan Corporate Social Responsibility (CSR) pada Perusahaan Sektor Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Periode 2021–2024 - Zulfa Khoirul Ummah; Suhesti Ningsih; Suprihati Suprihati (Lembaga Yasin AlSys, 2026)
This study was motivated by post-pandemic financial pressure in the telecommunications sector and inconsistencies in previous research findings regarding financial factors that influence corporate social responsibility disclosure. This study aims to analyze the influence of profitability measured through Return on Assets (ROA), liquidity measured through the Current Ratio (CR), and leverage measured through the Debt to Equity Ratio (DER) on Corporate Social Responsibility (CSR) disclosure. This study employed a quantitative approach with a causal-associative design. The research sample was determined through purposive sampling, resulting in 16 telecommunications sector companies listed on the Indonesia Stock Exchange for the 2021–2024 period, with a total of 64 observations. Secondary data sourced from annual reports and sustainability reports were analyzed using multiple linear regression through SPSS 23 after meeting the classical assumption tests. The results showed that profitability, liquidity, and leverage each had a positive and significant influence on CSR disclosure. Simultaneously, the F-test results showed that the three variables had a significant influence on CSR disclosure, with a coefficient of determination of 54.6%. The conclusion of this study affirms that corporate social transparency does not merely represent regulatory compliance but also forms part of a business strategy influenced by cash flow stability, profitability, and debt management. The implications of this study indicate that management needs to maintain fundamental financial performance to ensure the sustainability of CSR programs, while investors can use CSR disclosure as one indicator in assessing investment risk and corporate sustainability.